Physicochemical Properties of Temperature-/pH-Sensitive Hydrogel Materials - Magdalena Bańkosz; Katarzyna Sala; Klaudyna Grzela; Dominika Wanat; Korneliusz Rzepka; Monika Iglar; Jakub Piątkowski; Aniela Woźniak; Magdalena Kędzierska; Bożena Tyliszczak (Engineering Proceedings, 2023)
This paper presents the synthesis of fluorescein-modified hydrogel materials. The obtained materials were characterized using FT-IR spectroscopy. Then, their sorption capacity in distilled water and Ringer’s liquid was determined. Using digital microscopy, the morphology of the obtained systems was characterized.